2014
DOI: 10.1021/nn501479e
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 Quantum Dot-Interspersed Exfoliated MoS2 Nanosheets

Abstract: We report the synthesis of heterodimensional nanostructures of MoS2 quantum dots interspersed in few-layered sheets of MoS2, using a liquid exfoliation technique in organic solvents. This unique hybrid morphology results from the optimized experimental conditions involving bath sonication followed by ultrasound probe sonication. We show that such heterodimensional hybrid materials could easily be extracted from the solvent as precipitates when post-treated with less polar volatile solvents such as chloroform. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
467
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 671 publications
(508 citation statements)
references
References 39 publications
36
467
0
5
Order By: Relevance
“…Zhang et al presented a combination of grinding and sonication techniques to prepare TMDC QDs from their bulk crystals [14]. Similar exfoliation in aqueous solution instead of organic solvents has also been reported [15]. However, defect-free WS2 has been difficult to obtain, and imperfections including sulfur vacancy defects and oxidized impurities may strongly affect the transport properties of the materials [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…Zhang et al presented a combination of grinding and sonication techniques to prepare TMDC QDs from their bulk crystals [14]. Similar exfoliation in aqueous solution instead of organic solvents has also been reported [15]. However, defect-free WS2 has been difficult to obtain, and imperfections including sulfur vacancy defects and oxidized impurities may strongly affect the transport properties of the materials [16,17].…”
Section: Introductionmentioning
confidence: 97%
“…On the contrary, blue-shift in A 1g peak may result from the strain experienced during the PAA-MoS 2 formation and/or stacking-induced electrodeposition process, which probably causes the surface reconstruction where weak interlayer interaction in MoS 2 can affect the intralayer bonding as well as lattice dynamics [32,33]. Moreover, it has been also shown that the frequency difference ( ) of two characteristic Raman modes increases with the thickness, which can be used to identify the MoS 2 layer number [8,32,[34][35][36]. In this context, the measured [32,36].…”
Section: Ionic Strength Induced Electrodeposition Of Paa-mos 2 and Itmentioning
confidence: 99%
“…QDs derived from 2D materials, including graphene,2 graphic‐C 3 N 4 ,3 MoS 2 ,4 and phosphorene,5 display several advantages, such as photostability and low toxicity in par with the conventional organic fluorophores and semiconductor QDs 6. Given their novel optical and electronic properties, 2D material‐derived QDs have widespread applications in bioimaging,7 photodynamic therapy,8 photo‐/electrocatalysis,9 photodetection,10 and sensing 11.…”
Section: Introductionmentioning
confidence: 99%